Urinary concentrations of bisphenol A in relation to biomarkers of sensitivity and effect and endocrine-related health effects - Yang, Mihi; Kim, Soo-Young; Chang, Seong-Sil; Lee, In-Seon; Kawamoto, Toshihiro (Environmental and molecular mutagenesis, 2006)
The impact of endocrine‐disrupting chemicals (EDCs) on human health is not yet clear because of difficulties in ascertaining their biological effects. In the present study, we evaluated exposure to the EDC, bisphenol A (BPA), in 172 Koreans in relation to biomarkers of susceptibility and effect. The subjects completed questionnaires, which documented occupation, education, lifestyle factors, potential sources of BPA‐exposure, and the occurrence of self‐diagnosed endocrine disorders. None of the subjects were occupationallay exposed to BPA; however, urinary levels of conjugated BPA, determined by HPLC/FD, ranged from 0.03–62.4 μg/l (median, 7.86). The frequencies of potential susceptibility biomarkers, the UGT1A6‐Arg184Ser and the SULT1A1‐Arg213His polymorphisms, were not associated with urinary BPA levels, either as single genes or in combination. Indirect effects of BPA exposure on the susceptibility to mutagens were evaluated by comparing urinary BPA concentrations with MNNG‐induced sister‐chromatid exchange (SCE) in lymphocytes cultured from the subjects. BPA exposure showed marginal or significant associations with theSCEs induced by the low doses of MNNG (0–0.4 mM). However, there was no overall association between urinary BPA levels and MNNG‐induced frequency at doses ranging from 0.2–0.6 mM. Finally, we did not detect an association between urinary BPA concentration and endocrine‐related disorders. Even though we were unable to find a strong association between BPA exposure and a biological response, possibly because of the limited number of subjects, we observed that most of the subjects were exposed to BPA. Therefore, continuous biological monitoring of BPA is a prudent measure to prevent possible BPA‐related health risks. Environ. Mol. Mutagen., 2006. © 2006 Wiley‐Liss, Inc.